Nephroprotective effects of polyherbal extract via attenuation of the severity of kidney dysfunction and oxidative damage in the diabetic experimental model - Kausar, Mohd. Adnan; Parveen, Kehkashan; Siddiqui, Waseem A.; Anwar, Sadaf; Zahra, Aqeela; Ali, Abrar; Badraoui, Riadh; Jamal, Azfar; Akhter, Naseem; Bhardwaj, Neha; Saeed, Mohd (Cellular and Molecular Biology, 2022)
In view of many complications of diabetes, kidney failure is considered as one of the main complications. The oxidative stress-induced due to persistent hyperglycemic conditions is the major cause of kidney disease. The present study was designed to explore the nephroprotective efficacy of polyherbal (PH) extract in a diabetic model induced by streptozotocin (STZ). STZ (55 mg/kg body weight, intraperitoneal) was injected in overnight fasting rats to develop the diabetic experimental model. Effect on kidney injury was evaluated by investigating biochemical and histological evidences in renal tissue after 56 days of treatment of PH extract. Results showed the high glucose level in STZ treated rats that suggested hyperglycemia persistence along with the successful establishment of nephropathy in diabetic rats with altered renal function, inflammatory cytokines level as well as oxidative and nitrosative stress. Administration of PH extract significantly improved the glycemic condition, glomerular function and proximal reabsorptive markers. Further, elevated pro-inflammatory cytokines levels and disturbed redox status were restored. Moreover, findings were fostered and substantiated by histopathological examinations. Our work strongly proposes that the nephroprotective effect of the PH extract on renal damage could be attributed due to its anti-inflammatory and antioxidant properties. Thus, PH extract could have potential as a pharmaceutical drug for diabetes mellitus (DM). Additional long-term study or clinical trial is required for further investigations.